Extracorporeal photopheresis in paediatric patients: A retrospective comparison between different 'off‐line' protocols. Issue 10 (14th September 2022) - Sebastián, Elena; Andrés Esteban, Eva María; González‐Vicent, Marta; González de Pablo, Jesús; Zubicaray, Josune; Gálvez, Eva; Guillén, María; Ruiz Pato, Julia; Molina, Blanca; Albi, Gustavo; Ramírez, Manuel; Castillo, Ana; et al.
Abstract: Background and Objectives: Extracorporeal photopheresis (ECP) has been shown to be an effective treatment for graft‐versus‐host disease (GvHD). However, information regarding lymphocyte collection for ECP in children is limited. The aim of this study was to analyse and compare lymphocyte collection for ECP in children using different devices and protocols. Moreover, we have studied both safety and variables of the infused product related to treatment efficacy. Patients and Methods: This was a retrospective study of 91 patients who underwent 1524 apheresis procedures with either the COBE Spectra or Spectra Optia system. The comparison study between the Optia protocols (MNC and CMNC) was prioritized. We analysed 578 procedures using the Optia blood cell separator: 204 and 374 using the MNC and the CMNC protocol, respectively. Results: The Optia CMNC protocol showed better collection efficiency, with increased lymphocyte collection per kg of body weight ( p < 0.001). On multivariate analysis, the type of protocol showed no relationship with haematocrit or platelet loss. Most procedures were well‐tolerated, with the most frequent adverse events related to venous access (21.7%). Seventy‐one percent of patients had either partial or complete clinical GvHD response. In the multivariate model, only two variables were associated with a better response to ECP, younger age and a greater increase of B lymphocytes after treatment. Conclusion: Lymphocyte collection for ECP is well‐tolerated in most children, achieving complete or partial response in more than half of GvHD patients. CMNC is the optimal software to perform lymphocyte collection in children.